Evaluation of Bus Rapid Transit System: Riyadh city, Saudi Arabia - Alshehri, Ahmed Mohammed (Journal of engineering sciences and information technology, 2023)
Al Riyadh city, the capital of the Kingdom of Saudi Arabia, is experiencing significant economic and population growth, it is also a major metropolitan area in Saudi Arabia and in the Gulf regions. This has led to a high level of car ownership and use of vehicles, and this has led to the construction of a series of slow-moving roads and roads around the city. Traffic congestion is a major problem, where road behavior has an economic and psychological impact on people. The Riyadh Bus stations and Bus Rapid Transit (BRT) System Project is an integral part of the current Riyadh metropolitan area including the new Riyadh Metro. The main objective of this paper’s is to study the “Bus Rapid Transit” network in the city of Al Riyadh and to assess the functioning of this network using geographic information systems and the theory of graphs.A centralized geodatabase has been built for BRT lines and stations. A geometric network was conducted for BRT routes to facilitate moving from any location to another within Riyadh city. The assessment and evaluation of BRT routes focused on routes and station distribution regarding Riyadh city and how BRT solved population needs in Riyadh city. Using the powerful GIS network analysis functions, a navigation system was developed to assist passengers in planning their trips from one station to another giving detailed information about route directions and different BRT lines used.The study reinforces the value of good design techniques for accessible public transportation systems. The utilization of accessible vehicles, such as low-floor buses, is needed but lacking for such an accessible system, planners and operators should be aware.
Keywords: Transportation network; Traffic conjunction; BRT; GIS Network Analysis